2021
DOI: 10.1038/s41598-021-00612-z
|View full text |Cite
|
Sign up to set email alerts
|

The effects of low pH on the taste and amino acid composition of tiger shrimp

Abstract: Recent research has revealed that shrimp sensory quality may be affected by ocean acidification but we do not exactly know why. Here we conducted controlled pH exposure experiments on adult tiger shrimp, which were kept in 1000-L tanks continuously supplied with coastal seawater. We compared survival rate, carapace properties and flesh sensory properties and amino acid composition of shrimp exposed to pH 7.5 and pH 8.0 treatments for 28 days. Shrimp reared at pH 7.5 had a lower amino acid content (17.6% w/w) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Besides, its crude protein content increases with water temperature and dietary protein content. , The bighead carp (Arischthys nobilis) cultivated in cold water reservoir has a wider range of unsaturated fatty acid species, higher levels of total polyunsaturated fatty acid esters (eicosapentaenoic acid, docosahexenoic acid, and arachidonic acid), and an umami taste . The amino acid content of tiger shrimp cultured under pH 7.5 is significantly lower than that of tiger shrimp cultured under pH 8.0, especially the Glu and Asp acid responsible for umami . Among these environmental factors, high alkalinity is an important environmental factor characteristic of saline–alkali water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, its crude protein content increases with water temperature and dietary protein content. , The bighead carp (Arischthys nobilis) cultivated in cold water reservoir has a wider range of unsaturated fatty acid species, higher levels of total polyunsaturated fatty acid esters (eicosapentaenoic acid, docosahexenoic acid, and arachidonic acid), and an umami taste . The amino acid content of tiger shrimp cultured under pH 7.5 is significantly lower than that of tiger shrimp cultured under pH 8.0, especially the Glu and Asp acid responsible for umami . Among these environmental factors, high alkalinity is an important environmental factor characteristic of saline–alkali water.…”
Section: Discussionmentioning
confidence: 99%
“…36 The amino acid content of tiger shrimp cultured under pH 7.5 is significantly lower than that of tiger shrimp cultured under pH 8.0, especially the Glu and Asp acid responsible for umami. 37 Among these environmental factors, high alkalinity is an important environmental factor characteristic of saline−alkali water. The changes in alkalinity have no effect on the growth, feed conversion rate, and survival rate of Oncorhynchus mykiss, 38 but Chinese mitten crab (Eriocheir sinensis) under high alkalinity (10 mmol/L) aquaculture has better nutrition.…”
Section: Environmental Factors Have a Significant Impact On The Flavo...mentioning
confidence: 99%
“…Predicted increases in the magnitude of short-term environmental extremes and the frequency of conditions that are outside species' tolerance ranges under climate change (Kerr, 2011) highlight the importance of short-term (i.e. weeks to months) experiments for quantifying species-specific responses (as applied here; Jentsch et al, 2007;Thompson et al, 2013). However, the physical effects of climate change on marine systems also include underlying shifts in mean environmental conditions.…”
Section: Resilience Of Portunus Armatus Flavour Active Compounds To E...mentioning
confidence: 99%
“…However, studies integrating analyses of aroma-and tasteactive compounds with formal assessments of seafood appearance, aroma and taste by trained assessors are required to provide a mechanistic understanding of the impacts of nearfuture climate change on the sensory quality of seafood. A recent study by Hsieh et al (2021) found that exposing tiger shrimp (Penaeus monodon) to lowered pH reduced production of the amino acids glutamate and aspartic acid, which provide a umami flavour in seafood. These changes in amino acid production were subsequently supported by a blind sensory quality test, where P. monodon that had been exposed to lower pH received lower scores for flavour, appearance and texture.…”
Section: Changes To Volatile and Non-volatile Compounds Affect The Fl...mentioning
confidence: 99%